Locally ϕ-Symmetric Generalized Sasakian-Space Forms - Sarkar, A.; Sen, M. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
The aim of the present paper is to find necessary and sufficient conditions for locally ϕ-symmetric generalized Sasakian-space forms to have constant scalar curvature, η -parallel Ricci tensor, and cyclic parallel Ricci tensor. Illustrative examples are given.